Behavioural Finance –A study on its Bases and Paradigms - Sharma, Dhruva Jyoti; Sarma, Dr. Nripendra Narayan (International Journal of Scientific Research and Management (IJSRM), 2022)
Traditionally rational models have been chosen in the field of economics and finance. Experimental psychology has provided the behavioural insights in finance and economics. Behavioural finance is a new field which explains the economic decisions of people. It is a field which combines behavioural and cognitive psychological theories with conventional economics and Finance. In this paper efforts have been made to provide a framework for the concept related to the behavioural finance. Review of literature is carried out so that different dimensions and views regarding behavioural finance can be understood. Theories, models and studies which try to complement behavioural finance studies are also discussed. New frontiers and approaches that can be adopted for further studies are discussed and it may help to provide a conceptual framework for future studies.Key Words: Behavioural Finance, Theories, Models, Conceptual Framework